2011
DOI: 10.1097/nor.0b013e31821130d8
|View full text |Cite
|
Sign up to set email alerts
|

Inexpensive Alternatives for Extremity Cast and Bandage Protection

Abstract: Cast and bandage protector bags that are available commercially are often used by patients to keep their splints dry while in the shower. Garbage bags are considered a less expensive, but cumbersome alternative to these commercially available bags. We report a case of a 22-year-old man who has discovered that newspaper bags serve as easy to use covers for casts and bandages that are essentially free. Inexpensive alternatives to commercially available cast and bandage protector bags such as newspaper bags, disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Cast Cover (CVS Caremark, Woonsocket, Rhode Island), and Limbo (Thesis Technology Products, West Sussex, England) 10 .…”
mentioning
confidence: 99%
“…Cast Cover (CVS Caremark, Woonsocket, Rhode Island), and Limbo (Thesis Technology Products, West Sussex, England) 10 .…”
mentioning
confidence: 99%
“…Patients tried to find solutions to this problem, including wrapping cellophane around the plaster, and keeping the leg with the plaster cast out of the shower. Naram et al (2011) stated that the plaster should be protected from water and suggested inexpensive alternative materials for doing this such as newspaper and umbrella bags, as well as disposable plaster protection bags. Patients stated that they had difficulty using assistive devices, as even with the devices (e.g., crutches) they still feared falling.…”
Section: Self-image Challengesmentioning
confidence: 99%
“…According to Cieza et al (2020), at 436 million, fractures are the second most prevalent musculoskeletal disorder. Plaster casts have been used in the treatment of fractures since 1850, and they play an important role in the healing of operative repairs (Ekwall et al, 2018; Naram et al, 2011). In fractures treated with plaster casts, the bone alignment is corrected and this alignment is maintained by limiting mobility (Naram et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation